Pemodelan Struktural Niat Implementasi Standar Halal Pengusaha UKM Pangan Berdasarkan Faktor Teknologi, Organisasi, dan Lingkungan - Ida Giyanti; Anita Indrasari (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2019)
The objective of this study is to model the technological, organizational, and environmental factors influencing the intention of food manufacturing Small Medium Enterprises (SMEs) to fulfill halal standard requirements. The research was conducted in Surakarta city in which halal-certified SMEs became the research object. Data were analyzed using Structural Equation Model-Partial Least Squares (SEM-PLS). Technological factors were measured by the perceived benefit and complexity of the halal procedure. An organizational factor was measured by SMEs awareness towards the halal standards. While the environmental factor was measured using external pressure. The result shows that the estimated model found support only for the role of perceived benefit of halal standard implementation in influencing the intention of food manufacturing SMEs to fulfill halal standard requirements. Other hypotheses were in the predicted direction but not statistically significant. A little less than half (R2 = 0.413) of the variability in the intention to fulfill halal standard requirements is explained by the four variables. The structural model in this study has a predictive relevance at a moderate level with a Q2 value of 0.208. Based on the findings of this study, it is expected that the government always explains the benefits of adopting a halal standard to the food manufacturing SMEs. Theoretically, this study makes a contribution to enriching the research literature regarding halal certification adoption factors among food manufacturing SMEs.